2020
DOI: 10.1016/j.anihpc.2019.12.003
|View full text |Cite
|
Sign up to set email alerts
|

A counterexample to the Liouville property of some nonlocal problems

Abstract: In this paper, we construct a counterexample to the Liouville property of some nonlocal reaction-diffusion equations of the formwhere K ⊂ R N is a bounded compact set, called an "obstacle", and f is a bistable nonlinearity. When K is convex, it is known that solutions ranging in [0, 1] and satisfying u(x) → 1 as |x| → ∞ must be identically 1 in the whole space. We construct a nontrivial family of simply connected (non-starshaped) obstacles as well as data f and J for which this property fails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Yet, u is not identically 1 in the whole set double-struckRNK. The question of whether it is possible to construct nontrivial counterexamples will be addressed in a forthcoming paper , where it will be shown that smooth simply connected obstacles can be constructed so that the Liouville type property fails.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, u is not identically 1 in the whole set double-struckRNK. The question of whether it is possible to construct nontrivial counterexamples will be addressed in a forthcoming paper , where it will be shown that smooth simply connected obstacles can be constructed so that the Liouville type property fails.…”
Section: Resultsmentioning
confidence: 99%
“…We point out, however, that in such domains (see Figure 3) there might exist stable patterns which do not satisfy (22) but satisfy lim |x|→+∞ u(x) = 0. See also [10] for similar conclusions if the domain is a cylinder with varying cross section, and [14,15] for the case of non-local diffusion.…”
Section: Link With Minimal Surfaces Consider Equation (1) With the Rescaled Allenmentioning
confidence: 79%
“…This is a consequence of the fact that (P ∞ ) satisfies a Liouville type property, see Figure 3. (e) t = 600 (f) t = 750 (g) t = 900 (h) t = 1000 However, the authors have shown in [18] that there exist obstacles K as well as a datum (J, f ) for which this property is violated, i.e. such that (P ∞ ) admits a non-trivial solution u ∞ ∈ C(Ω) with 0 < u ∞ < 1 in Ω.…”
Section: Large Time Behaviourmentioning
confidence: 99%
“…Remark 2.8. The distance δ ∈ Q(Ω) in Corollary 2.7 may be chosen to be either the Euclidean or the geodesic distance, see [18]. See Figure 4 for an example illustrating the conclusion of Corollary 2.7.…”
Section: Large Time Behaviourmentioning
confidence: 99%
See 1 more Smart Citation